Resource management for intercropping white yam (diocorea rotundata poir) in coconut garden - Suja G (Department of Agronomy, College of Agriculture, 2001)
lntercropping Asiatic yamsviz., greater yam (Dioscorea alata) and lesser yam (Dioscorea esculentalui coconut gardens is a common practice. The recently introduced African white yam (Dioscorea rotundata), despite its superior tuber yield and quality has not yet found an appropriate place in the coconut based cropping system. Field experiments were conducted at College of Agriculture, Vellayani during 1998-99 and 1999-2000 to assess the performance of white yam variety Sree Priya as an intercrop in coconut garden, to evaluate the effect of growth promoting substances on sprouting and to standardize plant population, sett size and nutrient management practices for white yam under intercropping situation. Five growth promoting substances (thiourea 2%, potassium nitrate 2%, IAA 1000 ppm, wood ash and cowdung si urry) and a control were evaluated for their effects on sprouting of white yam setts in CRD. Sett treatment using thiourea 2% induced early, uniform and better sprouting and established a vigorous crop. Factorial combination of three spacings (60x60 cm, 75x75 cm, 90x90 cm) and three sett sizes (100 g, 200 g, 300g) arranged in RBD comprised the second experiment. Planting white yam setts of size 200 g at a spacing of90x90 cm so as to accommodate 9000 plants ha' of coconut garden resulted in better sprouting and canopy size, higher harvest index, optimum tuber yield and higher profit. The response of white yam to three organic manures (FYM,coir pith compost and in situ green manuring using sunhemp) assigned to main plots and combination of three levels each of nitrogen and potassium (40,80, 120 kg ha') apart from noko control in subplots was tested in split plot design, Application of coir pith compost increased vine length, number of functional leaves, LA!, leaf, vine, tuber and whole plant biomass, NAR, CGR, and plant uptake ofN and K. Coir pith compost application led to marked improvements in tuber quality by enhancing dry matter, starch and crude protein contents. There was no conspicuous